Experimental evaluation of Langmuir probe sheath potential coefficient on the HL-2A tokamak. (1st February 2018) - Nie, L.; Xu, M.; Ke, R.; Yuan, B.D.; Wu, Y.F.; Cheng, J.; Lan, T.; Yu, Y.; Hong, R.J.; Guo, D.; Ting, L.; Dong, Y.B.; et al.
Abstract: Systematic calibration experiment of Langmuir probe sheath potential coefficient Λ, which is a critical coefficient for estimating plasma sheath potential, has been carried out in the HL-2A tokamak deuterium plasmas. The electron energy probability function (EEPF) shows that electron outside last-closed-flux-surface (LCFS) is Maxwell distribution, but inside LCFS it changes to bi-Maxwell. Two kinds of plasma potential measuring method and three kinds Λ estmating method were compared. It is found that the estimated Λ coefficient is in the region of 2–3 outside LCFS and then increases to 5 inside LCFS due to the high temperature electron effect. Fortunately, the results show that the commonly used value Λ = 2.8 is still available to calculate plasma potential when we use the overestimated electron temperature measured by three-tip probe in bi-Maxwell case. Further analysis indicated this value should be corrected. Or it may lead to a error when we calculate the the electric field E r and its shear d E r / d r . The corrected value monotonically increased from 2.2 to 2.9 while Langmuir probe moved from 40 mm outside LCFS to 20 mm inside LCFS.